2017
DOI: 10.1080/13548506.2016.1274411
|View full text |Cite
|
Sign up to set email alerts
|

The impact of polyvictimisation on children in LMICs: the case of Jamaica

Abstract: a department of child and adolescent health, University of the West indies, Kingston, Jamaica; b University of north carolina at chapel hill, chapel hill, nc, Usa ABSTRACTChildren who experience polyvictimization in high-income countries (HICs) are at higher risk for mental health-related trauma symptoms. There is limited information on the impact of polyvictimisation on children with high levels of exposure, as occurs in some low-and middle-income countries (LMICs). This study investigates the impact of poyvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…These results may be showing that the protective factor of HRQoL associated with parental educational level would be only effective in low violence exposure settings. These findings are congruent with previous studies that found a higher impact of violence exposure over adolescents’ HRQoL [ 42 , 54 ], and partially congruent with studies that found better HRQoL and well-being among participants from rural areas (or less violent settings) and belonging to higher levels of parental education families [ 8 , 43 ]. It is difficult to connect these results with previous literature since little research has been conducted connecting violence exposure and subjective well-being scores in children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results may be showing that the protective factor of HRQoL associated with parental educational level would be only effective in low violence exposure settings. These findings are congruent with previous studies that found a higher impact of violence exposure over adolescents’ HRQoL [ 42 , 54 ], and partially congruent with studies that found better HRQoL and well-being among participants from rural areas (or less violent settings) and belonging to higher levels of parental education families [ 8 , 43 ]. It is difficult to connect these results with previous literature since little research has been conducted connecting violence exposure and subjective well-being scores in children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…The results related with mental health are congruent with studies conducted in the Brazilian adolescent population exposed to violence in which female adolescents reported higher levels of anxious and depressive symptomatology such as sleep disturbances and having feelings of loneliness [ 22 ]. Negative effects on mental health outcomes experienced by children in Jamaica have also been shown in regard with violence exposure [ 43 ], being this finding congruent with the presented results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Creating safety nets and publically funded systems for children also has a key role to play in developing cognitive capital. Failing to create safe environments for children and subsequent exposure to violence reduces intellectual functioning (Samms-Vaughan & Lambert, 2017). In highincome countries, exposure to violence is associated with reduced intellectual functioning and academic achievement (Gilbert et al, 2009;Jonson-Reid, Drake, Kim, Porterfield, & Han, 2004;Lansford et al, 2002).…”
Section: Returns On Investmentmentioning
confidence: 99%